Яруу найрагч Б.Лхагвасүрэнгийн “Сонгомол шүлгийн түүвэр”-ийг хятад хэлнээ орчуулсан орчуулгын зарим онцлог: Some Characteristics of the Chinese Translation of Poet B.Lkhagwasűren’s Collective of Selected Poems - G., Galbayar; B., Gegeenkhuu (Mongolian Journal of Foreign Languages and Cultures, 2023)
Khasan, a translator of the Chinese National Language Translation Bureau, selected 100 poems from Mongolian poet B. Lkhagwasüren’s collected works in Uyangyn Toirog [Lyric Circle] and Gashuun Öws [Bitter Herbs], and translated them into Chinese, publishing them in 2020 as Songomol shülgiin tüüwer [A Collection of Selected Poems by B. Lkhagwasüren]. In this article, first we examine the criteria the translator followed in selecting poems to be included. Then, based on an analysis of several examples, we examine how the translator translated the figurative usage of metaphor in the poems in selecting and translating the clear imagery of Mongol life and culture in B. Lkhagwasüren’s poems into Chinese. Finally, we reach the conclusion that Khasan has accurately and skillfully rendered metaphoric imagery relating to Mongol life and cultural characteristics in B. Lkhagwasüren’s poems.